KUALITAS PEMBANGUNAN MANUSIA DI PROVINSI PAPUA - Eleonora Sofilda (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
Various economic literature has been widely disclosed that the level of income, the allocation of the education budget, the level of investment and infrastructure spending are fundamental factors directly affecting the level of poverty. In the end, reducing poverty levels is expected to improve the quality of human development. The purpose of this study is to look at the effect of education budget allocation, health budget allocation, infrastructure budget allocation, population, open unemployment rate and inflation on poverty levels in Papua Province and see the effect of poverty levels on HDI in Papua Province. This study uses quantitative methods to analyze the effect of independent variables on HDI with poverty as an intervening variable in Papua Province. Data was taken from 2010-2017 and came from 29 regencies in Papua Province in Indonesia. The analytical tool used is Multiple Linear Regression with Panel Data. The findings of this study are significant education and health budget allocations to poverty levels, whereas for infrastructure allocation budgets, the population is not significant to poverty levels. Open unemployment and inflation are significant for poverty levels. Poverty Level Installed is very significant on the Human Development Index